Uncovering the hidden bacterial ghost communities of yeast and experimental evidences demonstrates yeast as thriving hub for bacteria - B. Indu; Tallapragada Keertana; Sahu Ipsita; Uppada Jagadeeshwari; Chintalapati Sasikala; Chintalapati Venkata Ramana (Scientific Reports, 2021)
Abstract Our major concern was to address “yeast endobacteria” which was based on a few reports in the recent past where bacteria may find yeast as a niche for survival. In this study, we report the microbiota of twenty-nine axenic yeast cultures recovered from different habitats based on their 16S rRNA gene-amplicon metagenomes. Yeasts were identified based on D1/D2 or ITS gene sequences. Bacterial diversity was widespread, varied and rich among all yeasts except for four strains. Taxa belonging to the phylum Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes and the genera; Streptococcus, Propionibacterium were common to all the yeasts. Candida tropicalis was used as a model organism to confirm bacteria through fluorescence in situ hybridization (FISH), isolating and re-introducing the isolated bacteria into the yeast. FISH analysis confirmed the endobacteria of C. tropicalis and we have successfully isolated four bacteria only after lysis and disruption of yeast cells. These bacteria were identified as species of Pseudomonas, Chryseobacterium, Lysinibacillus and Propionibacterium. Guestimates indicate 95% of bacterial species of C. tropicalis are yet-to-be-cultivated. We have successfully reintroduced mCherry tagged Pseudomonas into C. tropicalis. Also, auto-fluorescent Prochlorococcus and Rhodopseudomonas could be introduced into C. tropicalis while mCherry tagged E. coli or Salmonella could not be introduced. FISH analysis confirmed the presence of both native and infected bacterial cells present in C. tropicalis. Our findings unveil the insights into the ghost microbiota associated with yeast, which otherwise are considered to be axenic cultures. Their inherent occurrence, together with co-cultivation experiments under laboratory conditions suggests that yeasts are a thriving hub for bacterial communities.